2020
DOI: 10.1002/essoar.10504119.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slope-aspect induced climate differences influence how water is exchanged between the land and atmosphere

Abstract: Solar radiation differences generate different microclimates across adjacent northand south-facing slopes in the midlatitudes.• High-frequency measurements document microclimate and covarying tree water use across a hillslope divide over a dry Mediterranean summer.• Transpiration of a single tree species is higher on the drier, sunnier south-facing slope, suggesting different water use strategies.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…While primarily focused on determining the importance of soil type and geomorphology of the region, the study's most prominent finding is that shrubs growing on east and east north east facing slopes had significantly higher total plant volume and distance between neighbors than on any other slope face. Slopes in the region studied by Gearon and Young [2021] were much less steep, on average, than those studied by Bilir et al [2021]. Thus, such an extreme gradient in light environment or available soil moisture would not expected.…”
Section: Microclimate Morphology and Ecosystem Structurementioning
confidence: 75%
See 3 more Smart Citations
“…While primarily focused on determining the importance of soil type and geomorphology of the region, the study's most prominent finding is that shrubs growing on east and east north east facing slopes had significantly higher total plant volume and distance between neighbors than on any other slope face. Slopes in the region studied by Gearon and Young [2021] were much less steep, on average, than those studied by Bilir et al [2021]. Thus, such an extreme gradient in light environment or available soil moisture would not expected.…”
Section: Microclimate Morphology and Ecosystem Structurementioning
confidence: 75%
“…Yet, during times of soil dry down (soil water content < 4.5%) latent heat flux (LE) as measured by identical abovecanopy eddy covariance systems in each forest is up to 25% greater in the unaltered forest than in the disturbed (Figure 1). In an in silico 'forcing condition swap' between the two sites, similar to that performed by [Bilir et al, 2021], it was shown that these differences were unable to be accounted for by the minor differences in temperature, light, vapor pressure deficit, or soil water conditions between the two forests [Matheny et al, 2014]. The hydraulic strategies, defined as the distinct patterns of water acquisition, storage, and use, of the principle tree species comprising each plot were indicated as the most probable cause for the sustained differences in LE during Figure 1: A comparison of the percent difference in total ecosystem latent heat flux (LE) between the unaltered control forest and the disturbed forest as measured by eddy covariance systems in each stand.…”
Section: Accepted Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Rivendell, the study hillslope where rock moisture is measured, is 0.3 km upstream from the mouth of Elder Creek, and has been the site of intensive hydrological (Oshun et al, 2016;Salve et al, 2012;Schmidt & Rempe, 2020;Vrettas & Fung, 2015), ecological Link et al, 2014;Simonin et al, 2014;Tune et al, 2020), and geochemical (Bilir et al, 2021;Druhan et al, 2017;Kim et al, 2017)…”
Section: Site Descriptionmentioning
confidence: 99%